ENGLISH LEARNING DIFFICULTIES - Citra Utami; Intan Nuriatama; Nuriana Nuriana; Emeliya Sukma Dara (ANGLO-SAXON: Jurnal Ilmiah Program Studi Pendidikan Bahasa Inggris, 2022)
In this research article, the author analyzes the difficulties of students in learning English in . The SMA Budi Satrya Medan. focus of this research is to find students' difficulties in understanding the material presented and remembering the material from previous learning. The study is done by taking 10 students from the eleventh grade BudiSatrya. This study uses a classical and individual approach in collecting qualitative and quantitative data. The data obtained were obtained from the results of student learning exploration in the classroom and conducting interviews with students. The results show that the difficulty of learning English in the classroom is determined by how the teacher conveys the material. In connection with the research results obtained, it is suggested that teachers can use learning methods that are preferred by students so that students get a high sense of motivation to learn English in the classroom.